Effect of Ca2+ on weak cross-bridge interaction with actin in the presence of adenosine 5'-[gamma-thio]triphosphate). - Kraft, T (1992)
In the presence of the nucleotide analog adenosine 5'-[gamma-thio]triphosphate (ATP[gamma S]), effects of Ca2+ on stiffness and equatorial x-ray diffraction patterns of single skinned fibers of the rabbit psoas muscle were studied. It is shown that cross-bridges in the presence of ATP[gamma S] have properties of the weak-binding states of the ATP hydrolysis cycle. Raising the Ca2+ concentration up to pCa 4.5 has little effect on actin affinity of cross-bridges in the presence of ATP[gamma S]. However, the rate constants for cross-bridge dissociation and reassociation from and to actin are reduced by about 2 orders of magnitude. In addition, nucleotide affinity of the cross-bridge is much smaller at high Ca2+ concentrations. Implications for interpretation of fiber stiffness recorded during isotonic shortening and the rising phase of a tetanus are discussed.